Analysis of Purity and Concentration of DNA Isolation Results on Chondroitin Samples - Sri Utaminingsih; Alfi Sophian (BiosciED: Journal of Biological Science and Education, 2022)
Analysis of purity and concentration of isolated DNA is a way to see the quality of isolated DNA. This research was conducted as an initial stage to give. Information about research conducted in future research. The purpose of this research is to provide references and information regarding DNA isolation techniques in chondroitin samples, so that they can be used in similar studies. The sample consisted of a sample of chondroitin which was weighed 50 mg and tested 10 times. The isolation method used in this study is the centrifuge column isolation method, while the purity and concentration analysis were analyzed using a nano photometer which was read at a wavelength of A260/A280. The value shown from the nano photometer was then analyzed statistically using the average test to determine the interpretation of the results from the data obtained. The results of DNA isolation obtained that the DNA concentration values ​​tested were in the range of 39.10 - 54.70 with an average concentration value of 45.15. The value of the purity of the isolated DNA tested was in the range of 2.16 – 2.28 with an average purity value of 2.22. Based on the results of the DNA confirmation test of the isolation carried out using real-time PCR, it showed that the isolated sample was amplified at a value of Ct 36.43 while the positive control was amplified at Ct 32.49. Based on the research results, it was found that all samples tested showed good average values ​​of DNA concentration and purity so that the results of the DNA isolation tested could be used as templates in real-time PCR analysis.